A new genus and a new species of Anabropsinae (Orthoptera: Anostostomatidae) from China - Wang, Han-Qiang; Liu, Xian-Wei (Zootaxa, 2020)
A new species of a new genus Melanabropsis. tianmuica gen. & sp. nov. is described from China. 3 Japanese species of Anabropsinae are transferred to the new genus. A key to the Chinese genera of subfamily Anabropsinae is given. Materials are deposited in Shanghai Entomological Museum, Chinese Academy of Sciences.